“壽數”與“文化”的關聯度探析: Relevance of the Connection between Life Span and Culture - DENG, Rui (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Life span is affected by two important dimensions of traditional Chinese culture. The principle that “the Tao follows nature” makes Chinese philosophers tolerant of misunderstandings and frustration. Remaining calm and retaining a positive attitude can increase longevity. The obligation to “subdue the self” urges Chinese philosophers to concentrate on specific things, enabling outstanding achievements and even increasing longevity. However, culture is not the only determinant of life span. Social conditions also affect life expectancy. The comparison with French thinkers is one-sided, as individuals in numerous countries and professions enjoy a high life expectancy. Nevertheless, it is important to adhere to Confucian values to cultivate one’s moral character. DOWNLOAD HISTORY | This article has been downloaded 18 times in Digital Commons before migrating into this platform.